دور السلطة العليا للشفافية و الوقاية من الفساد ومكافحته في مجال الصفقات العمومية في الجزائر - عويشات, زكية (University of Eloued جامعة الوادي, 2021)
في ظل الانتشار الكبير للفساد المالي لا سيما في مجال الصفقات العمومية، والتّي تعتبر المجال الخصب لاستفحال ظاهرة الفساد، وباعتبارها الأداة القانونية التّي تعتمدها الدولة في تنفيذها لبرامجها الوطنية. وتنفيذ الاستراتيجية الوطنية للوقــاية من الفســاد، وتماشيا مع اتفاقية الأمم المتحدة لمكافحة الفساد، والتي صادقت عليها الجزائر، فقد عمل المشرع الجزائري إلى استحداث مجمــوعة من الوسائل القانونية المكــلفة بالوقــاية من الفسادومكافحته، لعل أبرزها الهيئة الوطنية للوقاية من الفساد و مكافحته. و نظرا لقصور دورها، خاصة فيما يتعلق باحترام قواعد الشفافية والنزاهة المتعلقة بإجراءات إبرام الصفقات العمومية، مما دفع بالمؤسس الدستوري إلى ترقيتها إلى سلطة عليا للشفافية والوقاية من الفساد و مكافحته،موجب التعديل الدستوري لسنة 2020، بحيث منحها مهام و صلاحيات واسعة تســاهم في تدعيــم دورها، وهذا تعزيزا لمبــادئ الشفـافية، والمساواة، إلى جانب تجسيــد مقومــات الحــكم الراشد في تسيير الشؤون العامة، وحماية الممتلكات والمال العام من التبديد. In light of the great spread of financial corruption, especially in the field of public deals, which is considered the fertile field for the rampant phenomenon of corruption, and as the legal tool adopted by the state in implementing its national programs. And in implementation of the national strategy to prevent corruption, and in line with the United Nations Convention against Corruption, and witchAlgeria has ratified, the Algerian legislator worked to develop a set of legal means in charge of preventing and combating corruption, most notably the National Authority for the Prevention and combating Corruption. Due to the shortcomings of its role, especially with regard to respecting the rules of transparency and integrity related to the procedures for concluding public deals, which prompted the constitutional founder to promote it to a supreme authority for transparency and the preventing and combating corruption, under the constitutional amendment of 2020, so that it is given broad tasks and powers that contribute to Strengthening its role this is in support of the principles of transparency and equality, as well as embodying the components of good governance in the conduct of public affairs, and the protection of property and public money from squandering.
مذكرة ماستر
Keywords: الصفقات العمومية، شفافية إجراءات إبرام الصفقات، السلطة العليا للشفافية و الوقاية من الفساد، الحكم الراشد.; Public deals, Transparency of procedures for concluding deals, the National Authority for the Prevention and combating Corruption, good governance.